Sistema de gestión de calidad para la obtención del certificado “Punto Verde” como beneficio para la empresa “Novopan del Ecuador” y la comunidad. - Flores Sandoval, Evelyn Geomara (2014)
The present investigation has the objective to analyze the Quality Management System of the company NOVOPAN DEL ECUADOR S.A., that is already applied, demonstrated and proven, the further investigation, analysis and improvement of the production processes that allow us to obtain the Ecuadorian Environmental Certification "PUNTO VERDE", which will provide a benefit not only for the company but also for the surrounding community. For this reason with a correct and detailed analysis and observation we are able to determine the requirements based on cleaner production, reduction of waste pollutants and mainly the reduction of the environmental impacts assigned by the Environmental Ministry, those that through environmentally certifiable projects and applied to the productive process will show the responsibility and the ethics that the company has with the care and preservation of the environment in which it involves.